(untitled) (World Bulletin of Social Sciences, 2021)
This article describes the information on the establishment of the Centers in Uzbekistan, the implementation of experimental tests in the field of broadcasting, the measures carried out to revive the work on radio broadcasting, as well as the information on the activities organized for the purpose of obtaining the school of economic knowledge and advanced experience of the population